2019
DOI: 10.1097/jcp.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Paliperidone Palmitate Treatment in Patients With Schizophrenia

Abstract: Purpose The aim of the study was to assess efficacy and safety of paliperidone palmitate (PP) in schizophrenic patients using real-life data. Methods This national, multicenter, retrospective, and mirror-image study was performed reviewing the medical records of patients in 18 centers. Adult schizophrenic patients receiving PP treatment (n = 205) were enrolled. Patients' data covering the last 12 months before the initial PP injection and the period unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Finally, only the study by [ 69 ] presented results on the effectiveness of LAI risperidone in a retrospective cohort study vs. all-oral SGAs and FGAs and vs. oral risperidone [ 69 ]. All the studies, including patients treated with PP1M, reported significant improvements in subjective well-being and global satisfaction, and improved personal and social performance [ 59 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 76 , 78 , 79 , 82 ]. Furthermore, functionality improvement was more remarkable in patients with a disease duration of 5 years or less [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, only the study by [ 69 ] presented results on the effectiveness of LAI risperidone in a retrospective cohort study vs. all-oral SGAs and FGAs and vs. oral risperidone [ 69 ]. All the studies, including patients treated with PP1M, reported significant improvements in subjective well-being and global satisfaction, and improved personal and social performance [ 59 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 76 , 78 , 79 , 82 ]. Furthermore, functionality improvement was more remarkable in patients with a disease duration of 5 years or less [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result revealed that full compliance patients had decreased hospital admissions and bed days. A multicenter mirror study in Turkey [ 53 ] revealed that the use of PLAI reduced the incidences of hospital visits because of relapse and the median number of hospitalizations. The Positive and Negative Symptom Scale score decreased over the course of PLAI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We identified and evaluated in 12 months before and after the rehabilitative program the following outcome indicators according to the Italian National State-Regions Agreement of cure program care [ 30 ] and literature data: number and duration of hospitalizations [ 31 , 32 ], continuity of care [ 33 ], adherence to LAI treatment [ 34 ], working condition and possible supported work services [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…LAI treatments and continuity of care, according to literature, reduced relapses and hospitalizations so represents a valid variable to evaluate the rehabilitative program efficacy [ 19 , 33 , 34 , 36 ].…”
Section: Methodsmentioning
confidence: 99%